2013
DOI: 10.4236/ojvm.2013.33033
|View full text |Cite
|
Sign up to set email alerts
|

Coccidiosis of Goats in Florida, USA

Abstract: Fecal samples from 277 goats on eleven farms in Florida were examined to determine the prevalence and intensity of the multiple species of Eimeria that infect goats in this region. The number of oocysts per gram of feces (OPG) was determined by the modified McMaster technique. Species identification was done following sporulation. Eimeria oocysts were found in 97% of the fecal samples. Goats less than one year of age shed significantly more oocysts than goats greater than one year of age (P < 0.01). Goats of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The mixed infection has been observed in study of Al-Bayati et al (2016) which were dealing with the same subject. The higher rate of mixed infections in goats was consistent with previous research reports as Kahan and Greiner( 2013) and Mohamaden et al( 2018) and could be attributed to the intensive management system which increased possibility of infection with various types of Eimeria spp. (Khodakaram-Tafti and Hashemnia, 2017).…”
Section: According Tosupporting
confidence: 90%
“…The mixed infection has been observed in study of Al-Bayati et al (2016) which were dealing with the same subject. The higher rate of mixed infections in goats was consistent with previous research reports as Kahan and Greiner( 2013) and Mohamaden et al( 2018) and could be attributed to the intensive management system which increased possibility of infection with various types of Eimeria spp. (Khodakaram-Tafti and Hashemnia, 2017).…”
Section: According Tosupporting
confidence: 90%
“…Değer et al [ 38 ] reported nine different species of Eimeria in goats from Turkey, these being E. arloingi , E. christensini , E. alijevi , E. hirci , E. ninakohliyakimovae and E. jolchijevi , in addition to E. pallida E. apsheronica and E. punctata . Nine species of Eimeria were also identified by Kahan and Greiner [ 40 ] in goats from Florida, USA. This group included both E. punctata and E. caprovina .…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those noted in Iran (83.4%) [ 31 ], India (79.2%) [ 32 ] and in Turkey (73.6%) [ 38 ]. A higher prevalence has been reported in Portugal (98.61%) [ 39 ], Florida, USA (97%) [ 40 ], China (92.9%) [ 41 ] and Spain (96.1%) [ 42 ]. However, all the cited works concerned research conducted on conventional farms.…”
Section: Discussionmentioning
confidence: 99%
“…In present study the high prevalence (≈98 %) of Eimeria infection was recorded in all examined goat farms which is in agreement with reports from other counties. In Poland Eimeria oocysts were found in 81 -100 % (Balicka-Ramisz, 1999), and in 95 % in Estonia (Lassen et al, 2013), 92 % in the Czech Republic (Koudela & Boková, 1998), 100 % in Slovakia, (Vasilková et al, 2004), 97 % in Florida, USA (Kahan & Greiner, 2013). Goat kids are particularly susceptible to the pathological effects of Eimeria infections, especially newly weaned kids kept in large numbers under intensive management conditions (Ruiz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%